Educational Leadership: Personality, Emotional Intelligence and Organizational Behavior (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
Leadership and organizational dynamics are vital for establishing an effective and sustainable educational setting. This research investigates how personal and organizational elements such as personality, values, perceptions, decision making, attitudes, job satisfaction, emotional intelligence (EI), resilience, and learning abilities impact leadership effectiveness and the performance of educational institutions. An extensive literature review revealed a significant connection between elevated emotional intelligence, robust resilience, and a leader's capacity to align organizational values with employee motivation and performance. Leaders in education who possess high emotional intelligence and strong resilience have demonstrated their ability to enhance job satisfaction, address conflict positively, promote inclusive decision making, and foster a culture of ongoing learning. The integration of these three components emotional intelligence, resilience, and value alignment serves as a crucial factor in enhancing leadership effectiveness and the overall performance of educational institutions. The findings show that leaders possessing this profile effectively foster an inclusive, adaptable, and growth focused workplace, which benefits employee well being and enhances student academic performance. Actionable suggestions consist of: creating leadership development programs aimed at improving emotional intelligence and resilience, establishing clear and inclusive communication practices, fostering an organizational culture rooted in common values and ongoing learning, and incorporating job satisfaction evaluations and decision making processes into assessments of leadership performance. Through the adoption of these suggestions, educational organizations can foster adaptive leadership capable of effectively confronting complex difficulties, thus attaining superior and sustainable performance.